Fail-Safe and Safe-Life Concepts Effects on the Safety Factor in Mechanical Design - Sergio Baragetti (Current Approaches in Science and Technology Research Vol. 10, 2021)
This chapter reports the study of the effects that the Safety Factor has on Fail-Safe and Safe-Life concepts. The study is focused on mechanical design but the same concepts might be applied to other scientific research fields. Fault tree analysis is considered and concept of components put in series or parallel deepened. The discussion develops through reliability, safety and randomness concepts.